Spy school goes north eaudiobook - Gibbs, Stuart (Spy School, 2023)
In the eleventh book in the New York Times bestselling Spy School series, Ben Ripley goes on a rescue mission when one of his own is abducted from a remote Alaskan training facility. Ben Ripley and his friends are training in Alaska when Cyrus Hale is kidnapped by his old Russian nemesis. Ben, Erica, and the others mount a rescue mission, but events quickly spiral out of control in a plot involving the secret history of US-Russian relations, a young KGB agent with skills to rival Erica's—and lots and lots of bears.